Smartphone-based portable device for multi-sample colorimetric determination of nitrite in sausage - Yenuthok, Aekgphoonnada; Saleepochn, Tharinee; Charnsethikul, Saijai; Sae-Heng, Thitilapa; Lowmunkhong, Pongsak (Agriculture and Natural Resources, 2025)
Importance of the work: A custom-designed light box with a hat-shaped cover ensured consistent illumination for image analysis using a smartphone-based method. Objectives: To develop a simple, rapid and accurate smartphone-based method for detecting nitrite in sausages. Materials and Methods: Samples were analyzed on a microplate and images were captured using a smartphone camera. Green color intensity was measured and correlated with the nitrite concentration. The method was validated against the Association of Official Analytical Chemists (AOAC) standard, demonstrating high sensitivity and accuracy. Results: Using the Griess reaction, the method formed an azo dye compound and provided a portable, user-friendly and cost-effective alternative to conventional techniques. A custom-designed photo box with LED lighting and a hat-shaped light fixture enabled simultaneous analysis of multiple samples. The method provided excellent sensitivity and accuracy, with a linear correlation between green color intensity and nitrite concentration. The addition of 0.003% Brilliant Blue solution substantially expanded the calibration curve’s linear range. Validation against the AOAC method confirmed the reliability of the method, highlighting its potential for rapid, on-site food analysis. Main finding: The custom-designed, hat-shaped light fixture effectively minimized specular reflections from Light emitting-diode lighting, enabling the use of cost-effective alternatives to iPads or tablets as illumination sources for simultaneous multi-sample colorimetric measurements.